2013
DOI: 10.1002/jgra.50551
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime ionospheric enhancements induced by the occurrence of an evening solar eclipse

Abstract: [1] The solar eclipse on 15 January 2010 traversed Asia and completed its travel on the Shandong Peninsula in China at sunset. Two vertical incidence ionosondes at Wuhan and Beijing and the oblique incidence ionosonde network in North China were implemented to record the ionospheric response to the solar eclipse. Following the initial electron density decrease caused by the eclipse, the ionosphere was characterized by a strong premidnight enhancement, and a subsequent ionospheric decay, and a~10 h later postmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…For instance, it seems unlikely that the posteclipse enhancement in the electron density can be explained by noneclipse effects, given that several other studies have reported similar posteclipse effects, both for this eclipse (e.g., Cherniak & Zakharenkova, 2018;Wu et al, 2018) and previous events (e.g., Chen et al, 2013). This also explains why there are signatures present in the observations already before the actual start of the partial eclipse: These are differences between 21 and 22 August 2017 that are unrelated to the eclipse.…”
Section: Comparison To Observationsmentioning
confidence: 93%
“…For instance, it seems unlikely that the posteclipse enhancement in the electron density can be explained by noneclipse effects, given that several other studies have reported similar posteclipse effects, both for this eclipse (e.g., Cherniak & Zakharenkova, 2018;Wu et al, 2018) and previous events (e.g., Chen et al, 2013). This also explains why there are signatures present in the observations already before the actual start of the partial eclipse: These are differences between 21 and 22 August 2017 that are unrelated to the eclipse.…”
Section: Comparison To Observationsmentioning
confidence: 93%
“…The critical frequency and peak height of the F 2 layer ( f o F 2 and h m F 2 ), as well as other ionospheric parameters, can be gained from the ionogram. The other seven observation locations at 120°E were selected from the detector locations of the oblique‐incidence ionosonde network in northern China, which was developed by the China Research Institute of Radio Wave Propagation [ Chen et al , ]. The 5 transmitters and 20 receivers comprise the oblique‐incidence ionosonde network.…”
Section: Observation Locations and Instrumentsmentioning
confidence: 99%
“…Thus, it may result in the downward ionization diffusion from the protonsphere [Evans, 1965b;Jakowski and Förster, 1995;Mikhailov et al, 2000]. The plasma flux will make up the electron loss, delay the ionospheric response to the solar eclipse, and even cause the electron density enhancement [Evans, 1965a;Jakowski et al, 2008;Chen et al, 2013]. As discussed by Evans [1965a] and Le et al [2008Le et al [ , 2009b, the rate of the plasma diffusion is proportional to the square of the local dip angle.…”
Section: 1002/2014ja020849mentioning
confidence: 99%
“…The disturbance from outside the ionosphere creates the indirect influence. The rapidly decreasing temperature in the lunar shadow may induce the downward plasma flux from the protonsphere and enhance the ionospheric electron content [Evans, 1965a;Chen et al, 2013]. When the solar eclipse passed the Earth's atmosphere, the cooling of the ozone layer in the stratosphere was shown as the major source of the gravity waves [Gerasopoulos et al, 2008;Girach et al, 2012;[Chimonas, 1970;Beer and May, 1972;Baulch and Butcher, 1977;Chen et al, 2011b].…”
Section: Introductionmentioning
confidence: 99%